Sublinear Time Algorithms - Rubinfeld, Ronitt; Shapira, Asaf (SIAM journal on discrete mathematics, 2011)
Sublinear time algorithms represent a new paradigm in computing, where an algorithm must give some sort of an answer after inspecting only a very small portion of the input. We discuss the types of answers that one can hope to achieve in this setting.